Indonesian Halal Product Certification Realization Strategy by the Halal Product Guarantee Organizing Agency (BPJPH) - Khayati, Ismatul; kalimah, Siti; Agustin, Riska (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The Halal Product Guarantee Organizing Agency (BPJPH) is implementing the mandate of the Ministry of Religion of the Republic of Indonesia which is targeting 10 million halal-certified products by October 2024 to make Indonesia the world's halal center. BPJPH has implemented various strategies to realize this target. Through this qualitative research, it was found that by early 2024 it had been realized that 4,591,573 products are halal certified. The strategy that best shows its optimality in achieving this realization is the existence of a self-declared halal certification registration route, the SiHalal application, and the Sehati program. With the success of the strategy and realization of halal certification, BPJPH won two awards from prestigious events in the field of Information Technology in the form of the TOP Digital Award 2023.